Facile fabrication of Co3O4/nitrogen-doped graphene hybrid materials as high performance anode materials for lithium ion batteries. Issue 19 (12th April 2016) - Li, Peihang; Cui, Mengnan; Zhang, Mingbo; Guo, Amin; Sun, Yunfei; Wang, Heng-guo; Li, Yanhui; Duan, Qian
Abstract : Novel hybrid materials of well-dispersed Co3 O4 nanoparticles with high density anchored on nitrogen-doped graphene are used as high-performance anode materials for lithium-ion batteries. Abstract : Novel hybrid materials of well-dispersed Co3 O4 nanoparticles with high density anchored on nitrogen-doped graphene (CNGs) are reported. The prepared CNGs show high performance as anode materials for lithium-ion batteries (LIBs), such as high initial discharge capacity (1080.9 mA h g −1 at 50 mA g −1 ), long cycling stability (a high reversible capacity of 867.9 mA h g −1 after 350 cycles), and high rate capability (155.6 mA h g −1 at 2 A g −1 ). The high performance arises from the synergetic effect of conductive nitrogen-doped graphene sheets and ultra-small Co3 O4 nanoparticles, which highlights the importance of the anchoring of the small sized nanoparticles on the doped graphene sheets for applications in LIBs.